A Corpus-Based Study of Metadiscourse Features Across Pctb Textbooks at Primary and Secondary Levels - Ghafar, Ata ul (American Journal of Literature Studies, 2022)
Metadiscourse markers (MMs) are linguistic features that scholars use to express their messages compellingly and persuasively. Metadiscourse not just aides the peruser to comprehend the essential message of the message through construction and content, rather its suggest the peruser with the specific inclinations and points of view in the essential talk.The basic purpose of this study is to explore metadiscourse markers division and frequency designed by Pakistani authors Punjab curriculum textbook board at primary and secondary level students for the academic year 2018-2019. And also try to encompasses appropriate and inappropriateness as well. An adhock corpus comprises at primary and secondary levels Punjab textbook board English language books. Ken Hyland's taxonomy Metadiscourse (2005) was selected to investigate the frequency of metadiscourse features though famous AntConc 3.5.8 software is used for text analysis. According to obtained results, interactive metadiscourse features has more frequently used rather interactional metadiscourse features in Punjab curriculum textbook board English language books.The total numbers of interactive markers are 10,429 likewise interactional metadiscourse markers total numbers are 94,91. The research indicates the worth of metadiscourse features in Punjab curriculum textbooks board English language books and opens the door for syllabus designers and researchers that they should considered the worth of metadiscourse in pedagogical perspective.